Ameloblastic fibrosarcoma of the maxilla with EGFR exon 20 insertions: Relevance of whole-exome sequencing in molecular understanding and therapeutic proposals for rare cancers. Issue 6 (December 2022) - Terada, Kazuhiro; Yamada, Yosuke; Ishida, Yoshihiro; Yamamoto, Takuya; Kikuchi, Masahiro; Nakashima, Yasuaki; Haga, Hironori
Abstract: Ameloblastic fibrosarcoma (AFS) is the most common odontogenic sarcoma, but the incidence is relatively low, and its molecular biology is poorly understood. We experienced a young female patient with a rapidly growing soft tissue tumor of the left maxilla, which eventually occupied the left side of the oral cavity. Histologically, the tumor mainly consisted of a proliferation of atypical spindle to polygonal cells without any specific differentiation, but a small number of benign odontogenic epithelial foci mainly in the tumor periphery were also noted; thus, a diagnosis of AFS was made. We performed whole-exome sequencing (WES) on the tumor to investigate its molecular features and identify therapeutic options. We found that the tumor harbored EGFR exon 20 insertions and MDM2 amplification; the former may be a target for newly developed tyrosine kinase inhibitors in case of recurrence. To the best of our knowledge, this is the first case of AFS for which WES was performed and with EGFR mutation. Our case provides new genetic information on AFS and suggests that comprehensive genetic analysis can clarify the molecular biology in rare cancers, potentially leading to the proposal of therapeutic strategies.